Analyze The Performance of Sharia Stock (Study at PT Wijaya Karya Persero Tbk) - Utami, Anita Dwi; Radia, Dewi Andita Permatasari; Mariana, Syafira (Journal of Business, Accounting and Finance, 2024)
One way to manage wealth is by investing. Investment can be done by buying shares. Shares are divided into two, namely conventional shares and sharia shares. The sharia stock market is a stock market where every transaction is carried out based on sharia principles. One of the companies that entered the sharia stock market is PT Wijaya Karya Tbk (PT WIKA). The company experienced a decline in net profit and net income during the Covid-19 pandemic so that investors became concerned about the stability of its shares. Signals from the company through financial performance provide information that shows the bank's performance is very high to the market so that it can attract the attention of investors. Descriptive analysis that will be used in this study. The object of research is Sharia Shares and PT WIKA Shares. The results of the study seen from the economic conditions, industrial conditions, and business conditions ofPT WIKA show that PT WIKA shares are worth buying even though during the Covid-19 pandemic there was a decline in net profit and net income. In addition, it is predicted that in the future it will get big projects, especially since the Indonesian government is currently intensively carrying out development.